EVALUASI PENANGGULANGAN WELLCONTROL MENGUNAKAN DRILLER’S METHOD PADA TRAYEK 6-1/8” SUMUR “X” LAPANGAN “Y” - Sahmil Habibi Harahap; Nugroho Marsiyanto; Wahyu Sutresno (Jurnal Bhara Petro Energi, 2026)
This study evaluates the effectiveness of the application of the driller's method on the 6-1/8" trajectory of the X well in the Y field using secondary data from drilling operations, namely the values ​​of SIDPP, SICP, ICP, FCP, mud volume, pump data, and Leak-Off Least (LOT) results. The method used is quantitative analysis and well control calculations carried out through the following stages: determining formation pressure, calculating Initial Circulating Pressure (ICP), Final Circulating Pressure (FCP), Kill Mud Weight (KMW), and evaluating the formation safety limit through MAASP and MADFD. The results showed that the actual mud weight of 14.2 ppg was underbalanced against the equivalent formation pressure of 14.5 ppg, thus triggering a kick. The calculation resulted in an ICP of 270 psi, FCP of 243 psi, and KMW of 14.39 ppg, while the LOT of 2195 psi indicated that the formation capacity was still safe for the circulation process. The evaluation concluded that the Driller's Method was effective and safe for use in mitigating kicks without causing lost circulation. as well as formation damage.